Presentation of Tuberculous Meningitis Patients : Study of 30 Cases (Medicine Today, 2013)
Tuberculosis is creating immense adverse social and economic burden in Bangladesh. Tuberculous Meningitis results from the haematogenous spread of primary or postprimary pulmonary disease or from the rupture of a subependymal tubercle into the subarachnoid space. Infection of the CNS is one of the most devastating clinical manifestations of tuberculosis This study aimed to see the presentation of tuberculous meningitis patients in tertiary level hospital of Bangladesh. This cross sectional study was carried out in the Department of Neurology, SSMC, Dhaka from June 2011 to July 2012. In the present study, thirty meningitis patients were enrolled, among the subjects 11.7 % were aged below 20 years, 53.3% were aged between 20 - 39 years, 16.7% were aged between 40 - 49 years and 18.3% were aged above 50 years. Regarding sex 56.7% were male and 43.3% were female. Most prevalent symptom was fever (91.7%). Among others, headache (70%), altered consciousness (45%), vomiting (43.3%) and neck stiffness (28.9%) were notable. The distribution of the study subjects by physical sign 55.0% had anemia, 95.0% had neck rigidity, 10.0% had cranial nerve palsy, 46.7% had kernig's sign and 20.0% had long tract sign. Regarding GCS score 10.0 % had GCS score less than 8, 18.3 % had between 9 12 and 71.7% had over> 12.The Laboratory finding among the study subjects 3.3% showed positive gram stain and 43.7% showed MT over 10 mm. In response to treatment 93.3% responded to anti TB out of 30 TBM subjects. This study demonstrated that presentation of tubercular meningitis is different in different patient.TBM is the severe form of extra-pulmonary tuberculosis occurring in 7.0- 12.0% of TB patients in developing countries with high rate of mortality due to delay in diagnosis and proper treatment. DOI: http://dx.doi.org/10.3329/medtoday.v25i1.16069 Medicine Today 2013 Vol.25(1): 32-35